Meningkatakan Kreativitas Melalui Pembelajaran Steam pada Anak Usia 5-6 Tahun di TK Negeri Pembina Kota Mojokerto - Putri Alisa Qotrun Nada; Rachma Hasibuan; Salamun Salamun (Journal on Education, 2023)
Early childhood education is a fundamental education for children and influences the development of further education, so it is necessary to introduce 21st century learning, namely STEAM from an early age which will build children's positive attitudes about STEAM because the growth and subsequent development of children is greatly influenced by what is given to them. child in the early days. This classroom action research aims to increase the creativity of children aged 5-6 years at TK Negeri Pembina Kota Mojokerto through STEAM learning so that children have 21st century skills and are used to solving problems actively, critically and creatively. From the results of this classroom action research, it was found that STEAM learning was able to increase children's creativity from the first cycle of 55.83% to 81.38% in the second cycle. Learning that has been implemented in cycle II is said to be successful because there is an increase in children's creativity in the form of being creative in making works and presenting results creatively based on STEAM which has met the indicators of success.